Clinical case of encephalitis with antibodies to NMDA receptors - L. U. Ulukhanova (Detskie Infekcii (Moskva), 2019)
Anti-NMDA receptor encephalitis is an autoimmune disease of the central nervous system caused by autoantibodies to the NR1 and NR2 subunits of the glutamate NMDA receptor, with the possibility of both death and rapid remission. The binding of these antibodies blocks receptors and causes slowly developing psychiatric disorders, motor disorders and seizures.Presented clinical observation in a 9-year-old patient. The disease debuted with prodromal flu-like symptoms, fever, headache and general weakness, after which neuropsychiatric symptoms, impaired memory and speech developed, further progression of the disease, convulsive status, and coma with a fatal outcome were noted. The final diagnosis of autoimmune encephalitis was made after identification of antibodies to the N-methyl-D-aspartate (NMDA) receptor in the blood.